Predicting Environmental Behavior at Polluted Rivers in Terengganu using Structural Equation Modeling - Wan Nor Azilawanie Tun Ismail; Aziz Amin (International Journal of Advanced Science and Technology, 2020)
Mismanagement of environmental sustainability issues especially on river quality shows an increase every year. As the environmental effects toward today’s and future generation that will have to depend on the protection of the ecosystem come in many ways, the need to create a more environmentally responsible society has risen. It is a duty to conserve water sources concerning its quality and quantity before they are completely wiped out. This study aims to identify the determinants of the behavior of people living in polluted rivers in Terengganu. This study was conducted in a quantitative approach using a survey method for data collection. A total of 373 respondents were selected by cluster sampling. The study site was conducted at ten rivers that were considered polluted in Terengganu. Instruments used to collect the data were questionnaire form and analyzed with software namely IBM Statistical Package for Social Science (SPSS) and Analysis of Moment Structure (AMOS). The findings show that knowledge and exposure to environmental messages through the media is a dominant factor influencing respondents’ behavior on river conservation. As a result, this study can form a united and positive civil society. It is vital to create a progressive society that cares about the environment and understands the needs of current and future generations